The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.conbuildmat.2020.118838
|View full text |Cite
|
Sign up to set email alerts
|

Self-heating and electrical performance of carbon nanotube-enhanced cement composites

Abstract: This work hypothesizes that mixing carbon nanotubes with cement improves the thermal and electrical properties of bulk cement composites. To test this, two different methods of combining cement and dispersed multi-walled carbon nanotubes (MWCNTs) were considered. In the first method, cement composites were produced by adding a dispersion of MWCNTs to cement. In the second, MWCNT-based thin films were spray-coated and combined with cement to produce cement composites. A third group of specimens was produced usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…As shown in Figure 4a, this was achieved by connecting the positive and negative poles of a DC power supply (EX-200) to the stainless-steel meshes inserted in the composites. A voltage of 60 V was supplied to each specimen for 60 min, which was selected because the highest temperature variation occurred at 60 V in the composites mixed with MWCNTs [34]. The temperatures of the composites generated by the applied voltage were measured by connecting the thermocouple to a static data logger (TDS-303).…”
Section: Experimental Programmentioning
confidence: 99%
“…As shown in Figure 4a, this was achieved by connecting the positive and negative poles of a DC power supply (EX-200) to the stainless-steel meshes inserted in the composites. A voltage of 60 V was supplied to each specimen for 60 min, which was selected because the highest temperature variation occurred at 60 V in the composites mixed with MWCNTs [34]. The temperatures of the composites generated by the applied voltage were measured by connecting the thermocouple to a static data logger (TDS-303).…”
Section: Experimental Programmentioning
confidence: 99%
“…The self-sensing ability of concrete is achieved by a change in the conductive network of the conductive material inside the concrete (Al-Dahawi et al, 2016a;Al-Dahawi et al, 2016b;Al-Dahawi et al, 2017;Yıldırım et al, 2018;Demircilioğlu et al, 2019;Yıldırım et al, 2020). Smart concrete is developed by adding carbon nanotube (Xing et al, 2016;Al-Dahawi et al, 2017;Gupta et al, 2017;Yoo et al, 2017;Yıldırım et al, 2018;Lee et al, 2020;Yıldırım et al, 2020), carbon fibers (Al-Dahawi et al, 2017;Yıldırım et al, 2018;Yıldırım et al, 2020), steel fibers (Le and Kim, 2017;Demircilioglu et al, 2020;Le and Kim, 2020), graphite nanofibers (Yoo et al, 2017), graphene (Al-Dahawi et al, 2016a;Al-Dahawi et al, 2016b;Al-Dahawi et al, 2017;Yoo et al, 2017;Birgin et al, 2020;Wang et al, 2020), nickel or hybrid materials (Azhari and Banthia, 2012;Konsta-Gdoutos and Aza, 2014) and other functional fillers. The research on CNT reinforced self-sensing cement-based materials is the most concentrated.…”
Section: Introductionmentioning
confidence: 99%
“…Yoo et al [23] found that MWCNTs had a better enhancement effect on the electrical conductivity of cement paste than graphite nanofibers (GNF) and graphene (G), and the fluidity of the composite had an effect on the resistivity of the material. Lee et al [24] found that the simultaneous addition of dispersed MWCNTs solution and MWCNTs base film to cement composites was able to better enhance the heating properties of the cement paste and obtain the lowest resistance. Cerro-Prada et al [25] studied the effect of four different mass fractions of MWCNTs on the strength and electrical properties of cement mortars.…”
Section: Introductionmentioning
confidence: 99%